HYPERTENSION MANAGEMENT WITH THE "AKSI" PROGRAM (Hypertension Control Activity) IN THE COMMUNITY - Kartika, Annisa Wuri; Zainusshalihin, Muhammad; Christanti, Magdalena Ayu; Agustina, Risa; Kusumawati, Diah Ika Milenia; Janah, Miftakhul; Dewi, Atma Taufika; Rosyidah, Lailatul; Pratama, Edo Apriliano; Nurazizah, Aini; Reihana, Afin Alamei; Budihaningrum, Asti Shelia; Putri, Alliya Avisa Insani; Amalia, Aura Tasya; Firdausi, Naila (Caring: Jurnal Pengabdian Masyarakat, 2023)
Hypertension is a non-communicable disease with a high incidence and is in first place for the ten most common diseases in Malang City in 2021-2022. The management of hypertension in the community is aimed at maintaining and improving health status by increasing the active role of the community in solving problems. This community service activity is carried out with the "AKSI" (Hypertension Control Activity) program which contains hypertension class activities and the application of complementary therapy to warm water foot soaks and ginger to lower blood pressure. This activity was conducted with 20 hypertension participants who participated in hypertension class activities for 4 meetings. Assessment of success was carried out by measuring knowledge and blood pressure on the pre-test and post-test. The activity results showed an increase in participants' knowledge with an average pre-test score of 60 increasing to 90 during the post-test. Meanwhile, in blood pressure, there was a moderate decrease in systole of 34 mmHg and an average decrease in diastolic of 11 mmHg. It is hoped that this activity will become one of the strategies for managing hypertension in the community.